The diverse impacts of COVID-19 on electricity demand: The case of Chile. (June 2022) - Sánchez-López, Miguel; Moreno, Rodrigo; Alvarado, Diego; Suazo-Martínez, Carlos; Negrete-Pincetic, Matías; Olivares, Daniel; Sepúlveda, Carlos; Otárola, Héctor; Basso, Leonardo J.
Abstract: This paper analyzes the impacts of the first wave of COVID-19 (March 2020 - September 2020) on the electricity demand of different types of consumers in Chile, including residential, commercial, and industrial demand. We leverage data from 230 thousand smart meters of residential and commercial consumers in 32 communes of Santiago (the capital city of Chile), which allows us to investigate the evolution of their demands with an hourly temporal resolution. Additionally, we use demand data of large industrial consumers provided by the Chilean system operator to study the impact of the pandemic on different economic sectors. This paper demonstrates that the COVID-19 pandemic, and the associated containment measures, have featured a drastically different impact on the various types of consumers in Chile. In particular, we show that the demand of residential consumers has increased throughout the first wave, even when we isolate the effects of the pandemic from those related to weather. Furthermore, we study how these effects change in different communes of Santiago, contrasting our findings with the socio-economic levels of the population. In effect, we find different demand response patterns depending on the socio-economic background of consumers. We also show that commercial demand has significantly declined due to the containment measures implemented and that the hospitality and construction economic sectors have been the most affected in the country. Highlights: The impacts of the COVID-19 on the electricity demand in Chile are quantified. Demands from residential, commercial, and industrial sectors are studied. The impacts significantly depend on the type of consumers. The impacts also depend on the socio-economic level of consumers. Hospitality and construction are the most affected economic sectors.